DESIGN AND ANALYSIS OF A MECHANICAL INTERFACE WITH POSE ADJUSTMENT FUNCTION OF MACHINE TOOL MODULES - WANG YongQuan; ZHANG GuangPeng; LEI JianMing (Jixie qiangdu)
Reconfigurable machine tools realize the processing conversion of each part in the part family through the exchange of its functional modules. However,due to the influence of machine structure layout and module weight,how to ensure the performance and accuracy of the machine tool under the condition that the modules are interchangeable is a difficult problem in the research field of reconfigurable machine tools. A mechanical interface device which can micro-adjust the module pose and ensure the stiffness of the machine tool is proposed in this paper. The comb-tooth joint surface and auxiliary supports used in the interface can realize the precise positioning and improve the connection stability between the machine-tool modules. The pose of the machine-tool module is adjusted slightly through the elastic-expansion-ball interface-unit deformation caused by the preload force exerted by the lock bolt on it. The preload deformation and connection stiffness of the interface unit are coordinated by different arrangement of the steel balls in it. The finite element analysis model of the mechanical interface is established,and the influence of different structure sizes and loading conditions on the stiffness characteristics of the mechanical interface is analyzed accordingly,which lays a theoretical foundation for the further application of the mechanical interface.